Opinion Paper: Initiation of Sustainability at Homes in Indonesia - Putra, Hendyansyah (Journal Research of Social Science, Economics, and Management, 2025)
The purpose of the study is to give perspective to readers and persuade them to act towards a better way of sustaining this one earth. The study focuses on how to contribute to national sustainability starting only from our own home. The method used in this paper is an Opinion Paper, where the writer gives his opinion and finds related supporting documents as secondary sources to summarize and provide the best opinion to readers related to sustainability as the topic. The results confirm that houses in Indonesia have a lot of potential to be a house lab for sustainability acts, since the number of households is huge. The writer also proposes the need for “gotong-royong” to support community sustainability in neighborhoods. More specifically, this will lead directly to national sustainability with the community helping and strengthening each other towards longevity. The implications of this research include: (1) Academic—providing a conceptual framework that integrates local culture into the global sustainability discourse; (2) Practical—offering a model of action that can be adopted by families and communities; and (3) Policy—serving as input for the formulation of a more participatory and community-based sustainability program. Thus, this paper emphasizes that the transformation towards national sustainability can start from grassroots initiatives strengthened by community collaboration.